Resultados neonatales y tipo de parto en gestaciones a término de acuerdo al registro cardiotocográfico. - Paccha Reinoso, Ronal Michael (2016)
The CTG registration is intended to prevent morbidity and mortality and maternal fetal avoiding unnecessary interventions limiting unnecessary iatrogenic prematurity and cesarean section. The design is observational, descriptive, cross-sectional cohort performed at the San Vicente de Paul Hospital in the city of Passage in the period from March to August 2016, with a universe of 501 and the sampling design of 89 pregnant women who met the criteria inclusion and exclusion, having as objectives: the relationship between a registry cardiotocographic and APGAR of the newborn in the first minute and fifth minute; Correlate the CTG registration with meconium; Registry cardiotocographic relationship with the route of delivery. Data collected from medical records were reflected in the data collection sheet obtained by the author: chi2 a value of 7.37 and p: 0.117 for the first minute APGAR chi2 4.65 and p: 0.09 for the fifth minute APGAR to establishing that there is no statistically significant relationship; there is no statistically significant relationship between CTG and amniotic fluid registration at birth, obtaining a value of chi2 6.10 and p: 0.41; the relation of the CTG registration and route of delivery is not statistically significant to obtain a value of chi2: 4.75 and p: 0, 093. Keywords: Record cardiotocographic, pregnant, neonatal APGAR